Engaging children to voice their sense of place through location-based story making with photo-story maps. Issue 2 (3rd March 2020) - Martz, Corey J.; Powell, Rebecca L.; Wee, Bryan Shao-Chang
ABSTRACT: Sense of place is neither linear nor rooted in time. One way for children to voice their sense of place is through location-based stories with plots structured in space, rather than time. Since mobile devices are already ingrained in the everyday lives of many children in the U.S., a mobile application offers a familiar medium to engage children in location-based story making. Here, we present photo-story maps, our approach to leveraging an existing story-map mobile application as a research tool to collect and analyze children's stories about sense of place. We found that photo-story maps facilitate the organization of nonlinear location-based stories, promote an inclusive story-making process through a mobile application, support triangulation of varied digital story elements, and provide dynamic interview material. We suggest photo-story maps demonstrate the value of location-based story making and the potential of familiar mobile applications for reducing the barriers to including children in research.